Abstract 070: Door in‐door out time for stroke thrombectomy transfers in a large hub‐and‐spoke network - Rashid A. Ahmed; Joyce A. McIntyre; Thabele M. Leslie‐Mazwi; Alvin S. Das; Adam A. Dmytriw; Joshua A. Hirsch; James D. Rabinov; Omer Doron; Christopher J. Stapleton; Aneesh B. Singhal; Natalia S. Rost; Aman B. Patel; et al. (Stroke: Vascular and Interventional Neurology)
Introduction The mantra ‘time is brain’ cannot be overstated for patients suffering from acute ischemic stroke. This is especially true for those with large vessel occlusions (LVO) requiring transfer to an endovascular thrombectomy (EVT) capable center. We sought to evaluate the spoke hospital door in‐door out (DIDO) times for patients transferred to our hub center for EVT. Methods Individuals who first presented with LVO to a spoke hospital and were then transferred to the hub for EVT were retrospectively identified from a prospectively maintained database from January 2019 to November 2022. DIDO was defined as the time between spoke hospital door in arrival and door out exit. Baseline characteristics, treatments, and outcomes were compared, dichotomizing DIDO at 90 min based in the American Heart Association goal for DIDO ≤90 min for 50% of transfers. Multivariable regression analyses were performed for determinants of 90‐day ordinal modified Ranking Scale (mRS) and DIDO. Results We identified 194 patients transferred for EVT with available DIDO. The median age was 67 (IQR 57‐80), and 46% were female. The median NIHSS was 16 (10‐20), 50% were treated with intravenous thrombolysis at a spoke, and TICI 2B‐3 reperfusion was achieved in 87% at the hub. The median DIDO was 120 min (97‐149), with DIDO ≤90 min achieved in 18%. DIDO was a significant determinant of 90‐day ordinal mRS (B=0.007, 95%CI=0.001‐0.012, p=0.013), even when accounting for last known well‐to‐spoke door in, spoke door out‐to‐hub arrival, hub arrival‐to‐puncture, puncture‐to‐first pass, age, NIHSS, intravenous thrombolysis, TICI 2B‐3, and symptomatic intracranial hemorrhage. Importantly, determinants of DIDO included Black race or Hispanic ethnicity (B=0.918, 95%CI=0.010‐1.826, p=0.048), atrial fibrillation or heart failure (B=0.793, 95%CI=0.257‐1.329, p=0.004), and basilar LVO location (B=2.528, 95%CI=1.154‐3.901, p<0.001). Conclusion In this real‐world analysis of a large hub‐and‐spoke network, spoke DIDO was the most important period of time for long term outcomes of LVO stroke patients treated with EVT. Determinants of DIDO were identified which require further investigation and motivate system changes that may reduce DIDO and improve patient outcomes.